TIPping the balance in adipogenesis: USP7-mediated stabilization of Tip60 - Gao, Yuan (Landes Bioscience, 2014)
Adipogenesis is regulated by a complex interplay between transcription factors, in concert with—among others—transcriptional cofactors, signaling cascades and miRNAs. Several studies have implicated the transcriptional cofactor and acetyltransferase Tip60 in PPARγ signaling and adipocyte differentiation. Since Tip60 protein levels, but not mRNA levels, are upregulated during adipogenesis, and since Tip60 can be degraded by the proteasome, we hypothesized that Tip60 protein may be stabilized through deubiquitination during adipogenesis. Indeed, Tip60 is protected from proteasomal degeradation by the deubiquitinase USP7, which is particularly important for mitotic clonal expansion (MCE), an early step in adipogenesis. Besides this novel role in early differentiation, earlier studies indicated that Tip60 is also important during the later stages of differentiation, indicating a dual role for this protein in adipogenesis. Our recent study sheds new light on the role of Tip60 in cellular differentiation and provide new insights into the importance of a regulatory process that has not been studied intensively in adipogenesis: protein (de)ubiquitination.